Quantifying the reaction mechanisms of a high-capacity CuP2/C composite anode for potassium ion batteries. Issue 10 (10th February 2021) - Zhao, Chen; Chen, Huixin; Liu, Haodong; Yin, Liang; Zhang, Qiaobao; Yu, Sicen; Liu, Ping; Zhong, Guiming; Lu, Can-Zhong; Yang, Yong
Abstract : The evolution process of various K–P alloys in a prepared CuP2 /C composite for potassium ion batteries is illustrated, revealing that PO x components in the composite are reversible. Abstract : Introducing metals into phosphorus to form metal phosphide materials as anodes for potassium ion batteries (PIBs) is an effective strategy to improve the electronic conductivity and alleviate the volume change during cycling, although with a compromise of capacity. Herein, we explore a CuP2 /C composite as a novel anode for PIBs, which delivers a high reversible capacity of >450 mA h g −1 . Unexpectedly, our results reveal that the PO x components existing in the prepared composite are reversible, through a quantitative analysis via high-resolution solid-state 31 P NMR and synchrotron X-ray diffraction tests. Their potassiation products K3 PO4 and K4 P2 O7 can react with K–P alloys and turn back to PO x during depotassiation, which probably accounts for the high capacity of the prepared material. The results also illustrate a crystallization–amorphization evolution process during cycling involving nanocrystalline α-K4 P6, K4 P3 and KP, and amorphous K4 P6, KP and K3 P phases, among which, the amorphous phases are identified for the first time.